Watching corresponding gestures facilitates learning with animations by activating human mirror-neurons: An fNIRS study. (April 2015) - Brucker, Birgit; Ehlis, Ann-Christine; Häußinger, Florian B.; Fallgatter, Andreas J.; Gerjets, Peter
Abstract: This study investigates whether displaying gestures that correspond to the depicted movements enhances learning about non-human biological movements with dynamic visualizations compared to displaying non-corresponding gestures. Functional near-infrared spectroscopy (fNIRS) was used to assess whether both types of gestures activate the human mirror-neuron system (hMNS). Low-visuospatial-ability learners benefited from corresponding gestures only, whereas high-visuospatial-ability learners achieved good results with both types of gestures. Accordingly, only low-visuospatial-ability learners showed higher activation of the inferior-frontal cortex (part of the hMNS) for corresponding than for non-corresponding gestures. Furthermore, low-visuospatial-ability learners watching non-corresponding gestures yielded better results when their inferior-parietal cortex (another part of the hMNS) was activated. Thus, three factors predict positive learning outcomes: higher visuospatial abilities, inferior-frontal cortex activation, and inferior-parietal cortex activation. In sum, activating the hMNS seems to facilitate learning about biological movements, and stimulating the hMNS by means of corresponding gestures might be an adequate instructional strategy to support low-visuospatial-ability learners. Highlights: High visuospatial ability fosters learning about non-human biological movements. For low-visuospatial-ability learners (LVSAL) the results are more differentiated. Corresponding gestures are better for LVSAL than non-corresponding gestures. Corresponding gestures activate for LVSAL areas of the human mirror-neuron-system. Additional neural processes of LVSAL can compensate for non-corresponding gestures.